Peran IPS dalam Meningkatkan Literasi Sosial dan Karakter Siswa - Ahmad, Ahmad (FKIP UNSULTRA, 2026)
Social Studies (IPS) plays a strategic role in developing social literacy and character in elementary school students, particularly in facing social challenges in the global and digital era. Social literacy encompasses the ability to understand social phenomena, think critically, and participate actively and responsibly in community life. Character education through IPS learning is directed at internalizing moral values ​​such as responsibility, empathy, honesty, tolerance, and social awareness. This study aims to comprehensively examine the role of IPS learning in improving social literacy and character in elementary school students through a literature study approach. The method used is a literature review by examining relevant national and international journal articles published between 2018 and 2025, obtained through Google Scholar, Sinta, and Scopus databases. The analysis was conducted descriptively and analytically by grouping research findings based on learning strategies, learning media, pedagogical approaches, as well as supporting factors and obstacles to IPS implementation. The study results indicate that social studies learning that integrates group discussions, case studies, problem-based learning, thematic learning, and the use of digital media and local wisdom has proven effective in improving social literacy and strengthening student character development. Furthermore, teacher competence, curriculum flexibility, the availability of learning media, and parental support are key supporting factors, while limited time, facilities, and teacher training are barriers to implementation. This study concludes that social studies is not only a cognitive subject but also a strategic tool in developing students with character, critical thinking, and social awareness. Further research is recommended to empirically examine the implementation of technology-based social studies and local wisdom.